Educational Psychology - Cline, Tony; Gulliford, Anthea; Birch, Susan (New York : Prentice Hall, 1951)
"Educational Psychology explores the role of the educational psychologist, firstly by examining cognitive development, cognitive psychology and individual differences and secondly through the analysis of social development and social psychology. Controversies and dilemmas in research and professional practice are discussed throughout the book. An initial chapter focuses on the development, contemporary nature and context of educational psychology as a profession, outlining especially the requirements for and the nature of professional training. Current debates and challenges are introduced within a diverse range of topics in cognition, learning and instruction, such as, intelligence, language development, dyslexia, maths anxiety, instructional psychology and inclusion. Similarly, topics covering social, emotional and behavioural issues in school - behaviour management and attributions, bullying, autism, school phobia, pupil identity and school ethos - are explored in terms of their roots in psychology theory and research and their high profile within public policy and decision making. The integrated and interactive approach, combined with the comprehensive coverage, make this book the ideal companion for courses in applied educational psychology"--
Preface : How can this book be used? / Tony Cline, Anthea Gulliford and Susan Birch -- What do Educational Psychologists do? / Susan Birch, Norah Frederickson and Andy Miller -- Evidence based practice in educational psychology : the nature of evidence / Anthea Gulliford -- What use is "intelligence"? / Tony Cline -- Raising educational achievement : what can instructional psychology contribute? / Anthea Gulliford and Andy Miller -- Inclusion for children with special educational needs : how can psychology help? / Nathan Lambert and Norah Frederickson -- Effective communication in school : do teachers and students talk the same language? / Tony Cline -- Can we cure dyslexia ? / Ben Hayes and Norah Frederickson -- Why does mathematics make so many people fearful? / Tony Cline -- Educating children with autism : what use is psychological theory and research? / Susan Birch and Norah Frederickson -- Managing classroom behaviour : perspectives from psychology / Anthea Gulliford -- School bullies : are they also victims? / Susan Birch and Norah Frederickson -- Coping with life by coping with school? : school refusal in young people / Anthea Gulliford and Andy Miller -- School ethos and student identity : when is wearing a uniform a badge of honour? / Tony Cline.
Revised edition of: Educational psychology / Norah Frederickson, Andy Miller, Tony Cline. London : Hodder Education, 2008.
Keywords: Educational psychology; EDUCATION / Educational Psychology; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Social Psychology